Plan de negocios para la creación de un parque de calistenia adaptado para personas con capacidades especiales - Beltrán Segovia, José David (2018)
"You cannot open your mind to others, if yours is not an open mind" - Masashi Kishimoto, Naruto Shippuden. In Ecuador, 2.6 percent of the population has some type of disability, which means that three out of every one-hundred people have a type of special capacity (CONADIS, 2017) The problem lies in the fact that many of these people have mobilization and adaptation problems due to non-adapted facilities. Additionally, all persons with and without disabilities must try to maintain a good state of health. (WTO, 2016). The present document presents an in-depth verification of the social and financial viability of the creation of a calisthenics park adapted for people with special disabilities that wants to solve this problem in sports. For this purpose, an in- depth investigation of external factors is carried out using PEST tools and Five Porter competitive forces, to verify the opportunities and threats of the environment through an EFE matrix. Subsequently, qualitative and quantitative research is carried out to gain understanding of the market. Based on this research, a marketing plan is made according to the needs and demands of the market, a correct design of all the necessary processes to be able to serve the client, and finally, a financial model is established to simulate and verify the viability of this project. With the results of this investigation, conclusions are drawn regarding all the important aspects that the project must have to fulfill the expectations of the consumers and to operate commercially and profitably.